(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The potential energy curves (PECs) of X¹Σ^+, a'³Σ^+, a³Π, A¹Π states for GeO molecule are calculated by the multireference configuration interaction method (MRCI) and MRCI with the Davidson's corrections (MRCI+Q) with aug-cc-pVTZ basis set. All these states involved dissociate into the same dissociation channel Ge(³P)+O(³P). For the four states, the spectroscopic parameters (R_e, D_e, ω_e, B_e, ω_eχ_e and T_e) have been obtained, which shows that our results are in very good agreement with the experimental value and other theoretical data at MRCI+Q level. The dipole moments of these states are also obtained. In addition, based on the accurate results of spectroscopic constants at MRCI+Q level, the first 30 vibrational states are determined for the four low-lying electronic states when J=0. The vibrational levels G(v) and inertial rotation constants Bv at MRCI+Q level are calculated when J=0, the results of X¹Σ^+ and A¹Π states are in concordance with the available other theoretical values and experimental work. The dissociation limits, dissociation energies, electronic configurations at equilibrium internuclear distance for a'³Σ^+, a³Π states also are predicted for the first time.